Estimates for Growth of Derivatives of Analytic Functions Along the Radius - Piddubnyi, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the radial boundary behavior of functions analytic in a unit disk of the complex plane.